FAMILY QUALITY OF LIFE: PARENTS OF CHILDREN WITH DISABILITIES (Annual of the Faculty of Philosophy in Skopje, 2024)
In recent years, there has been a growing emphasis on researching quality of life,particularly within families that include members with disabilities. Family Quality ofLife (FQOL) has gained prominence in special education as researchers seek to understandand improve the well-being of these families. This study aims to present findingson the quality of life of parents raising children with disabilities.Using a quantitative research approach and the validated BCFQOL tool, wesurveyed 205 parents. The results were unexpectedly positive, showing generally higherlevels of quality of life among participants. However, challenges were identified in specificdimensions such as “Emotional well-being,” and “Material well-being”.
Keywords: parents; child with disabilities; family quality of life